Charge transfer in (PbSe)1+δ(NbSe2)2 and (SnSe)1+δ(NbSe2)2 ferecrystals investigated by photoelectron spectroscopy. (5th January 2018) - Göhler, Fabian; Mitchson, Gavin; Alemayehu, Matti B; Speck, Florian; Wanke, Martina; Johnson, David C; Seyller, Thomas
Abstract: Rotationally disordered, layered (PbSe) 1 + δ (NbSe2 )2 and (SnSe) 1 + δ (NbSe2 )2 ferecrystal heterostructures, consisting of stacked two-dimensional bilayers of either PbSe or SnSe alternating with two planes of NbSe2, were synthesized from modulated elemental reactants. The electronic structure of these ternary systems was investigated using x-ray photoelectron spectroscopy and compared to the binary bulk compounds PbSe, SnSe and NbSe2 . The Pb and Sn core level spectra show a significant shift towards lower binding energies and the peak shape becomes asymmetric in the ferecrystals, while the electronic structure of the NbSe2 layers does not change compared to the bulk. This is interpreted in terms of an interlayer interaction in the form of a charge transfer of electrons from PbSe or SnSe into the NbSe2 layers, which is supported by valence band spectra and is consistent with prior results from transport measurements.